Comparison of benthic foraminifera and geochemical proxies in shelf deposits from the Upper Jurassic of the Prebetic (southern Spain) - Reolid, M.; Martínez-Ruiz, F. (Journal of Iberian Geology, 2012)
Comparison of the stratigraphic distribution of major and trace elements, used as proxies for palaeoproductivity and redox conditions, and benthic foraminifera from Oxfordian shelf deposits of the External Prebetic (Betic Cordillera, South Spain) allows us to recognise two sedimentary cycles, both characterised by initial enhanced productivity and decreasing oxygen availability in the seabottom, and a subsequent decreasing productivity with a recovering in oxygenation during the second half of each cycle. Dysoxic conditions appear to coincide with maximums in marine surface productivity, thus suggesting that oxygen depletion may be linked to greater consumption rather than restricted circulation. The boundary between the two cycles is characterised by low contents of redox-sensitive elements and lower TOC content and Sr/Al, P/Ti, Ca/Al and Ba/Al ratios, indicating well oxygenated sea-bottom, lower productivity and lower organic matter accumulation. The geochemical proxies have also revealed as a valuable tool for interpreting the stratigraphic fluctuations of benthic foraminiferal assemblages, as well as for evaluating the palaeoecology of the main genera. Spirillina is adversely influenced by oxygen depletion independently of food availability. Ophthalmidium presents very good correspondence with palaeoproductivity fluctuations, and tolerated low oxygen levels in the sediment-water interface. Reophax was an opportunist that proliferated after adverse conditions when oxygenation and food availability were limiting factors. The variability in the microhabitat depth inside the sediment of Reophax favoured adaptation to adverse conditions. Lenticulina shows behaviour similar to Reophax. Finally, Ammobaculites shows a low degree of relation with the palaeoproductivity proxies, and is intolerant with respect to low oxygen values in shallow infaunal microhabitats